2006
DOI: 10.1189/jlb.0905522
|View full text |Cite
|
Sign up to set email alerts
|

Detection and properties of the human proliferative monocyte subpopulation

Abstract: Peripheral blood monocyte subpopulations have been reported and can give rise to diverse, differentiated phenotypes. A subpopulation(s) of human monocytes can proliferate in vitro in response to macrophage-colony stimulating factor (M-CSF; or CSF-1). This population, termed the proliferative monocyte (PM), is presumably less mature than other monocytes; however, it has not been defined further. Previous studies monitoring the frequency of the slowly cycling PM from different donors indicated that the assay for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 52 publications
6
58
0
Order By: Relevance
“…We recently described the ability of CSF1 to generate a pure population of macrophages from pig bone marrow (2). Clanchy et al (31) carried out a detailed study of the proliferative response of human blood monocytes to CSF1 and demonstrated that around 30% of cells within the CD14 hi population could go through at least one cell division over 6-8 d. Although we have not quantitated the proliferative pool, the data in Fig. 2 suggest that cultivation in CSF1 leads to a very large increase in monocyte numbers in pig PBMC cultures, detected most effectively by expression of CD172a and the appearance of cells with increased size and granularity.…”
Section: Discussionmentioning
confidence: 99%
“…We recently described the ability of CSF1 to generate a pure population of macrophages from pig bone marrow (2). Clanchy et al (31) carried out a detailed study of the proliferative response of human blood monocytes to CSF1 and demonstrated that around 30% of cells within the CD14 hi population could go through at least one cell division over 6-8 d. Although we have not quantitated the proliferative pool, the data in Fig. 2 suggest that cultivation in CSF1 leads to a very large increase in monocyte numbers in pig PBMC cultures, detected most effectively by expression of CD172a and the appearance of cells with increased size and granularity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this proliferative subpopulation has a proinflammatory phenotype, since it could be the subpopulation that has most recently emigrated from bone marrow and that could also give rise to any proliferative macrophages in inflamed tissue (142). It has been reported that this relatively immature subpopulation is distinct from the CD14 low CD16ϩ population and contains osteoclast precursors (143). More information on human blood monocyte maturation and the possible trafficking of different populations during chronic inflammation is needed.…”
Section: Macrophage Lineage Heterogeneitymentioning
confidence: 99%
“…A subpopulation of human blood monocytes has been observed to proliferate in vitro in response to M-CSF and GM-CSF (141)(142)(143). It has been suggested that this proliferative subpopulation has a proinflammatory phenotype, since it could be the subpopulation that has most recently emigrated from bone marrow and that could also give rise to any proliferative macrophages in inflamed tissue (142).…”
Section: Macrophage Lineage Heterogeneitymentioning
confidence: 99%
“…In-vitro studies have demonstrated that M-CSF binds to the M-CSF (c-fms) receptor and induces the expression of genes in the osteoclast lineage leading to the differentiation and development of mature osteoclasts and cell survival (3,9). TNF-is an inflammatory cytokine that binds to the TNF receptors-1 and -2, stimulates osteoclastogenesis and regulates cell apoptosis (10). In addition osteoclast precursor cells express 2 integrins such as CD11b/Cd18) adhesion molecules that are necessary for cell trafficking and differentiation (11).…”
Section: Introductionmentioning
confidence: 99%